2021
DOI: 10.3390/s21113873
|View full text |Cite
|
Sign up to set email alerts
|

Field Test and Numerical Simulation on the Long-Term Thermal Response of PHC Energy Pile in Layered Foundation

Abstract: Investigation on the long-term thermal response of precast high-strength concrete (PHC) energy pile is relatively rare. This paper combines field experiments and numerical simulations to investigate the long-term thermal properties of a PHC energy pile in a layered foundation. The major findings obtained from the experimental and numerical studies are as follows: First, the thermophysical ground properties gradually produce an influence on the long-term temperature variation. For the soil layers with relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The geometric size, mesh density, and boundary conditions of the model are shown in Figure 4, in which a ground radius of 10 m and depth of 40 m were adopted to avoid the boundaries influencing the heat transfer. A vertical single U-shaped GHE with a radius of 110 mm and a depth of 30 m is set at the central position [35,36]. The clearance distance from the bottom side to the GHE should be larger than 10m to avoid the influence of bottom boundaries [37].…”
Section: Geometric Size Boundary and Initial Conditionsmentioning
confidence: 99%
“…The geometric size, mesh density, and boundary conditions of the model are shown in Figure 4, in which a ground radius of 10 m and depth of 40 m were adopted to avoid the boundaries influencing the heat transfer. A vertical single U-shaped GHE with a radius of 110 mm and a depth of 30 m is set at the central position [35,36]. The clearance distance from the bottom side to the GHE should be larger than 10m to avoid the influence of bottom boundaries [37].…”
Section: Geometric Size Boundary and Initial Conditionsmentioning
confidence: 99%
“…It is found that the existence of water in soil has a great role in promoting the efficiency of energy piles [9,[12][13][14]. It is also concluded that the pile diameter ratio, pile spacing, the diameter of the heat exchange tube in the pile, the water flow velocity in the pipe, the inlet water temperature, and the properties of the strata around the energy pile will affect the working efficiency of the energy pile [15][16][17][18][19][20]. In terms of the long-term working performance of the energy pile, the thermal cycle of the energy pile will lead to a decrease in the soil moisture content around the pile, resulting in a decrease in the thermal conductivity of the soil around the pile, which will increase the temperature around the energy pile and reduce the heat exchange efficiency of the energy pile [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of soil disturbance, such as displacement field, stress field, and disturbance range during pile driving is crucial for a comprehensive investigation of the disturbance effects of pile formation on the soil. On-site experiments [9][10][11][12], model tests [13][14][15][16], analytical solutions [17][18][19][20], and numerical simulations [21][22][23][24] have been carried out to investigate the effect of pile driving on soil disturbance. However, in terms of on-site experiments, current research is limited to the non-visibility of soil and embedded monitoring [9]; the obtained test results are not the entire displacement field, but rather local discrete points, which also affect the accuracy of the results.…”
Section: Introductionmentioning
confidence: 99%